2006
DOI: 10.1002/elan.200603635
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Copper at a Glassy Carbon Electrode Modified with Langmuir–Blodgett Film of p‐tert‐Butylthiacalix[4]arene

Abstract: A new type of voltammetric sensor, Langmuir -Blodgett film of p-tert-butylthiacalix[4]arene modified glassy carbon electrode, was advanced and used for determining copper at trace levels by differential pulse stripping voltammetry. Calibration plot was found to be linear in the range of 2 Â 10 À8 M to 5 Â 10 À6 M; the detection limit was 2 Â 10 À9 M. Possible recognition mechanism was also discussed. From determination of Copper in real samples (river, lake and tap water) it can be concluded that the method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Organic substances (OS) [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121], macrocyclic compounds [122][123][124][125][126], polymers [127-131, 157-159, 165-166, 169-175], bioactive compounds [186], and nanotubes [187][188][189][190] can also serve as GCE modifiers. Different combinations of the modifiers-a metal and OS [70-80, 97-105, 106], a polymer and a metal [86, 132-147, 160- [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] or the first modifying layer of mer...…”
Section: Glassy-carbon Electrodesmentioning
confidence: 99%
“…Organic substances (OS) [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121], macrocyclic compounds [122][123][124][125][126], polymers [127-131, 157-159, 165-166, 169-175], bioactive compounds [186], and nanotubes [187][188][189][190] can also serve as GCE modifiers. Different combinations of the modifiers-a metal and OS [70-80, 97-105, 106], a polymer and a metal [86, 132-147, 160- [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] or the first modifying layer of mer...…”
Section: Glassy-carbon Electrodesmentioning
confidence: 99%
“…Evtugyn and co-workers [29] designed a potentiometric sensor based on glassy carbon electrode covered with polyaniline and thiacalixarenes derivations and applied for determination of Ag + ions. We recently reported that GCE modified with a LB film of p-tert-butylthiacalix [4] [30,31]. In this approach, a glassy carbon electrode (GCE) modified with LB film of p-tert-butylthiacalix [4]arene is designed for the determination of trace amounts of Ag + .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have proposed a new idea of using LB film technique to modify calixarene derivatives on electrode as voltammetric sensors for recognizing and determining of metal ions. By this idea, we have reported of determining trace of Cu 2þ [30], Pb 2þ and Cd 2þ [31] with p-tert-butylthiacalix [4]arene LB film modifying GCEs and trace of Hg 2þ [32], Cd 2þ and Tl þ [33] with pallylcalix [4]arene LB film modifying GCEs, respectively. All of the detection limits of these metal ions reached below 10 À8 mol L…”
Section: Introductionmentioning
confidence: 99%